Optimalisasi Model Pembelajaran Kooperatif Tipe Think-Pair-Share untuk Meningkatkan Motivasi Akademik dan Prestasi Belajar Siswa dalam Mata Pelajaran Bahasa Indonesia di SD Pangeran Antasari Medan - Sri Ramadhani; Siti Rahmadhani Siregar; Amir Danis; Saut Mardame Simamora; Jusnizar Sinaga (Universitas Kristen Indonesia Toraja, 2025)
This study aims to examine the impact of implementing the Think-Pair-Share (TPS) cooperative learning model on improving academic motivation and learning achievement in Indonesian language lessons at SD Pangeran Antasari Medan. The TPS model was chosen because it encourages students to actively engage in discussions and collaborate, which can enhance their involvement in learning. The research method used is a quantitative approach with an experimental design, where data is collected through pre-tests and post-tests to measure changes in students' motivation and academic performance. In addition, a questionnaire was used to assess students' academic motivation. The results of the study show a significant improvement in both academic motivation and learning achievement after the implementation of the TPS model. Normality and statistical tests were conducted to ensure the validity of the data. This study provides benefits for the development of Indonesian language teaching at the elementary level by introducing a method that can effectively improve students' motivation and academic performance.